Pemanfaatan Sistem Informasi Geografis Untuk Zonasi Kawasan Pertambangan Kabupaten Ngawi - Yazid Fanani; Avellyn Shinthya Sari (PROMINE, 2018)
Ngawi regency has large potential of mining resources. However, there is no detailed data in mining arearegulation to optimalization of mining resources in Ngawi Regency. This research focus to identify miningresources in Ngawi Regency and making mining zonation used GIS aplication. Ngawi Regency Mining zonationmake with weighting and scoring in mining parameters than processing with overlay method. Based on thisresearch, Ngawi has 6 potential distribution mining resources, tehre is : Clay, Andesite, Limestone, Hard Soil,Sandstone, and Breccia. In Mining Parameters Ngawi Regency have 9 Parameters. Ngawi regency miningzonation can be divided into can be permitted to mined in 197 location, can be permitted to mined with certaincondition in 91 location , and can’t be permitted to mined in 254 location.